Generation and regulation of electromagnetic pulses induced by hybrid laser pulses interacting with solid targets. (1st June 2022) - He, Q.Y.; Deng, Z.G.; Meng, L.B.; Zhang, Z.M.; Cui, B.; Qi, W.; Yang, L.; Liu, H.J.; Fan, W.; Wang, C.K.; Yi, T.; Gu, Y.; et al.
Abstract: In inertial confinement fusion, electromagnetic pulses (EMPs) can be produced during high-power laser interacting with solid targets, which are intimately related to laser intensity and laser energy. In this study, EMPs generated by hybrid laser pulses coupling with targets are recorded and analyzed. The results indicate that a single picosecond laser gives birth to the most intense EMPs, but they are remarkably suppressed when a nanosecond laser-shooting target is triggered before the picosecond and femtosecond laser. One possible hypothesis is proposed based on x-rays inducing pre-ablation that generates pre-plasma at the surfaces of the picosecond target and femtosecond target, leading to a sharp drop both in the energy and number of the emitting hot electrons and protons. The findings will deepen our understanding of the mechanism of EMPs' generation and will also open a new avenue to regulate EMPs by hybrid laser pulses.